2012
DOI: 10.1016/j.bbrc.2012.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin, a polyether ionophoric antibiotic, inhibits adipogenesis

Abstract: The polyether ionophoric antibiotics including monensin, salinomycin, and narasin, are widely used in veterinary medicine and as food additives and growth promoters in animal husbandry including poultry farming. Their effects on human health, however, are not fully understood. Recent studies showed that salinomycin is a cancer stem cell inhibitor. Since poultry consumption has risen sharply in the last three decades, we asked whether the consumption of meat tainted with growth promoting antibiotics might have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…an ionophore and part of its mechanism of action is thought to involve the formation of lipid-soluble complexes with cations, thereby facilitating bi-directional ion flux through lipid barriers by passive diffusion. 9 Salinomycin can alter cytosolic calcium concentrations in rabbit hearts and was shown to inhibit mitochondrial function in isolated mitochondria. 7,10 Another study argued that salinomycin-induced increase of cytosolic Ca 2+ was partially mediated by influx through the plasma membrane and partially by release of Ca 2+ stored in mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…an ionophore and part of its mechanism of action is thought to involve the formation of lipid-soluble complexes with cations, thereby facilitating bi-directional ion flux through lipid barriers by passive diffusion. 9 Salinomycin can alter cytosolic calcium concentrations in rabbit hearts and was shown to inhibit mitochondrial function in isolated mitochondria. 7,10 Another study argued that salinomycin-induced increase of cytosolic Ca 2+ was partially mediated by influx through the plasma membrane and partially by release of Ca 2+ stored in mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, stress agents, such as ROS, were shown to regulate apoptosis, proliferation, differentiation, and inflammation in rabbit articular chondrocytes (22). Furthermore, Szkudlarek-Mikyo et al, reported that SAL regulates differentiation in adipocytes (18). However, there is a lack of data regarding the potential effects of SAL on differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…SAL is widely used in veterinary medicine and has recently been shown to regulate cellular responses in various cell types (18). The pharmacological action of SAL has generated increased attention in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Narasin, a cationic ionophore [1] with antimicrobial activity [2][3][4][5] is fed to ruminant animals to improve feed efficiency [6,7]. It may accumulate in tissues of edible animals [8,9].…”
Section: Introductionmentioning
confidence: 99%